Teachers’ Beliefs in Learners’ Autonomy in English Language Learning: A Case Study at MA Masdarul Ulum - Hayatun Nupus; Manalullaili Manalullaili; Winny Agustia Riznanda (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study was aimed at finding out teacher’s beliefs concerning learners’ autonomy in MA Masdarul Ulum. Qualitative research with case study study was applied by with two teachers of English of MA Masdarul Ulum as the participants. Observation and one-on-one interviews by using open-ended questions were administered to collect the data on teacher’s beliefs concerning learners’ autonomy in MA Masdarul Ulum. This study revealed the following: 1) Learner autonomy as the ability to understand and accepts responsibility for their own learning, 2) Teacher’s roles in developing learners’ autonomy were as a facilitator, counselor, resource, manager and organizer, 3) Teacher’s use group seating, and U-shaped can support cooperative learning that will help the students to develop their autonomy, 4) Indonesia current curriculum encourages the development of learner autonomy, and 5) The most effective way to practice learner autonomy in Indonesia are; hand-on exercise, small group discussion and project-based tasks to encourage collaborative learning